Effects of Sample Fixation on Specimen Identification in Biodiversity Assemblies Based on Proteomic Data (MALDI-TOF) - Rossel, Sven; Martínez Arbizu, Pedro (Frontiers in Marine Science, 2018)
Recently, MALDI-TOF mass spectrometry has been used to reliably identify taxonomically difficult harpacticoid copepods from sediment samples. In agreement with former studies, a negative impact of short storage periods was stated. Other studies reported inferior mass spectra quality from samples fixated in varying ethanol concentrations. Therefore, sediment samples from a mudflat sampling site in the North Sea were stored under different temperature conditions to explore a possible storage effect. Samples were fixated with either 70% or 100% ethanol and specimens were measured using MALDI-TOF mass spectrometry after one, two, three, five, seven and 12 weeks. The changes in number of peaks per species and the ability to identify specimens based on mass spectra were analyzed quality measurements. We show that storage temperature had a major impact on data quality, as for some species a loss of up to 50% of mass peaks and an increase of failed measurements to over 70% was observed. However, the effect of different ethanol concentrations on data quality was negligible. Concluding from these results, storage of metazoan samples in general and, particularly, of sediment samples at low temperatures of around -25°C is recommended to receive high-quality mass spectra for specimen identification.